2022
DOI: 10.1007/s40279-022-01762-4
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Blockade of Muscle Afferents and Perception of Effort: A Systematic Review with Meta-analysis

Abstract: École de kinésiologie et des sciences de l'activité physique (EKSAP) Centre d'éducation physique et des sports (CEPSUM)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 138 publications
0
17
0
Order By: Relevance
“…Under the current conditions, as outlined in the Methods section, we did not provide specific instructions to the participants to dissociate pain/discomfort from perceptions of effort (43), and therefore, the current RPE findings were likely at least partially influenced by afferent feedback from group III/IV free nerve endings stimulated in the active skeletal muscle (44,46). Thus, it is possible that the current RPE responses were more in line with perceived exertion as opposed to exclusively perceptions of effort (41,42,45,50), although there has been a previous critique related to the distinction between effort and exertion (62). Taken together, our results, in conjunction with previous reports, suggest that the lower cuff pressure most likely yields lower RPE values in healthy men and women, albeit perhaps only slightly lower, because of possible differences in magnitude and consistency of metabolic stress-related afferent feedback.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Under the current conditions, as outlined in the Methods section, we did not provide specific instructions to the participants to dissociate pain/discomfort from perceptions of effort (43), and therefore, the current RPE findings were likely at least partially influenced by afferent feedback from group III/IV free nerve endings stimulated in the active skeletal muscle (44,46). Thus, it is possible that the current RPE responses were more in line with perceived exertion as opposed to exclusively perceptions of effort (41,42,45,50), although there has been a previous critique related to the distinction between effort and exertion (62). Taken together, our results, in conjunction with previous reports, suggest that the lower cuff pressure most likely yields lower RPE values in healthy men and women, albeit perhaps only slightly lower, because of possible differences in magnitude and consistency of metabolic stress-related afferent feedback.…”
Section: Discussionmentioning
confidence: 98%
“…The current results indicated that collapsed across set and sex, the 60% AOP condition exhibited ~4% greater RPE responses than the 40% AOP cuff pressure. In addition, regardless of sex and cuff pressure, there was a linear increase in degree of perceived heaviness and strain experienced during the BFR bout as demarcated by the RPE values (40,42). It should again be mentioned that deoxy[heme] values were similar between the cuff pressures at the end of each set, which was when the RPE values were collected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the effort item on the NASA TLX (administered only after each bout) showed in no significant time effect. As effort differs from fatigue and other exercise‐related perceptions [for more information see 15 and 16 ], it is likely that, by rating separately fatigue and effort, as well as acquiring data between and within bouts, we were able to detect small changes in these two parameters. Differences with the literature could also be due to the greater sample size in this study, leading to a higher statistical power [29 vs. 9, 4 and 8 11 …”
Section: Discussionmentioning
confidence: 99%
“…The other model (central model) suggests that effort perception is determined by the processing of a copy of the central commands generated within the brain (De Morree & Marcora, 2015; Marcora, 2009). A recent meta‐analysis focused on studies investigating the effects of pharmacologically blocking III and IV muscle afferents on effort perception (Bergevin et al., 2022). The results discounted the role of afferent feedback from metaboceptive and nociceptive III and IV afferents and clearly showed that effort perception is determined by motor command‐related signals.…”
Section: Introductionmentioning
confidence: 99%